2020
DOI: 10.1038/s41581-020-0297-2
|View full text |Cite
|
Sign up to set email alerts
|

Plant-based diets to manage the risks and complications of chronic kidney disease

Abstract: Traditional dietary recommendations for patients with chronic kidney disease (CKD) focus on the quantity of nutrients consumed. Without appropriate dietary counselling, these restrictions can result in a low intake of fruits and vegetables and a lack of diversity in the diet. Plant nutrients and plant-based diets could have beneficial effects in patients with CKD: increased fibre intake shifts the gut microbiota towards reduced production of uraemic toxins; plant fats, particularly olive oil, have anti-atherog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
192
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(205 citation statements)
references
References 223 publications
(231 reference statements)
1
192
0
12
Order By: Relevance
“…Although plant and animal proteins differ in their AAs profiles, digestibility, and availability [11], these differences do not seem to be clinically relevant for the healthy adult general population with a varied and sufficient diet [88]. Indeed, the plasma AAs profile and in particular EAAs [89,90] of plant-based diets and animal-based diets is almost the same, except for a lower lysine-to-arginine ratio [91].…”
Section: Plasma Concentrations Of Amino Acids In the Context Of Plantmentioning
confidence: 99%
See 3 more Smart Citations
“…Although plant and animal proteins differ in their AAs profiles, digestibility, and availability [11], these differences do not seem to be clinically relevant for the healthy adult general population with a varied and sufficient diet [88]. Indeed, the plasma AAs profile and in particular EAAs [89,90] of plant-based diets and animal-based diets is almost the same, except for a lower lysine-to-arginine ratio [91].…”
Section: Plasma Concentrations Of Amino Acids In the Context Of Plantmentioning
confidence: 99%
“…There is extensive literature on the benefits of plant-diet in CKD progression and complications [11,12,18]. Based on these studies, we have summarized on Figure 1 the mechanisms of plant-based diets on CKD progression.…”
Section: Presumed Mechanisms Of Plant-diets Beneficial Effects On Ckdmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, studies have shown that adults who consumed more plant protein (PP) or plant-based diets such as Mediterranean, Dietary Approaches to Stopping Hypertension (DASH), or vegetarian, resulted in reduction of weight, glycated hemoglobin (HbA1C), low-density and high-density lipoproteins and total cholesterol and lower inflammation markers among adults with various chronic diseases [ 32 , 33 ]. Further studies have demonstrated that through the consumption of PP or plant-based foods there is a reduction in the incidence of CKD [ 34 ], inflammation markers (IL-6 and CRP) [ 35 ], uremic toxins, all-cause mortality, and hospitalization among the CKD population [ 20 , 36 ]. The potential mechanism of action is that, as the intake of plants is increased, and if possible as the sole source of energy and protein, the net dietary acid load is lowered.…”
Section: Introductionmentioning
confidence: 99%